First results of a survey concerning the use of digital human avatars in museums and cultural heritage sites - Sylaiou, Stella; Fidas, Christos (2022 International Conference on Interactive Media, Smart Systems and Emerging Technologies (IMET), 2022)
The paper presents the first results of a survey on the use of digital human avatars in museums and places of cultural interest. The papers included in this survey have been published between 2003 and 2022. The research questions examined were related to (a) the technological characteristics of Cultural Heritage-related uses of digital human avatars and patterns that emerge, (b) what affects their potential for audience engagement and (c) what directions may be suggested for future research based on the findings of this review.
Keywords: Avatars; Cultural differences; Emotion recognition; Media; Museums; Oral communication; digital human avatars; heritage sites; virtual museums